The Effectiveness of Using Artificial Intelligence in Advancing the Level of Biomechanical Analysis of Gymnastics Skills - Raheem, Ziadoon Salah (Pubmedia Jurnal Pendidikan Olahraga, 2026)
The research aims to identify the effectiveness of using artificial intelligence in advancing the level of biomechanical analysis of gymnastics skills by examining (the analytical efficiency of artificial intelligence in biomechanical measurement, temporal effectiveness and speed of data processing, objectivity and support of training decision-making, and the contribution of intelligent analysis to improving skill performance). The researcher used the descriptive method due to its suitability to the nature of the research. The researcher selected a random sample of (60) gymnastics coaches and relied on a questionnaire form to collect data. Among the most important conclusions was that the use of artificial intelligence in the biomechanical analysis of gymnastics skills demonstrates a high degree of efficiency and accuracy, contributes to reducing time and effort, enhances objectivity in evaluation, and supports the improvement of skill performance, which confirms its effectiveness as a modern scientific tool that can be employed to develop the training process in gymnastics. Among the most important recommendations was the necessity of expanding the use of artificial intelligence technologies in analyzing gymnastics skills within clubs and sports institutions, and integrating intelligent biomechanical analysis systems into daily training programs due to their role in improving evaluation accuracy and accelerating the analysis process.